High-risk human papillomavirus (hr-HPV) prevalence and abnormal cervical cytology in rural high-altitude communities: a population-based cross-sectional study in the Southern Tibetan Plateau, China (2023–2024) - Min Chen; Yeshi Lhamo; Kelsang Chödrön; Le Chen (Virology Journal)
Abstract Background Cervical cancer prevention remains challenging in resource-limited high-altitude regions. This study investigated the prevalence of high-risk human papillomavirus (hr-HPV) and cytological abnormalities in southern Tibet, China. Methods A population-based cross-sectional study (2023–2024) enrolled 21,112 women from the Shannan Region (altitude: 3500–6000 m). The participants underwent hr-HPV genotyping (16/18 and 16 other types) and ThinPrep cytologic testing (TCT). Statistical analyses included χ² tests and quadratic regression. Results The overall hr-HPV prevalence was 9.57% (2,021/21,112). Non-16/18 types predominated (83.37% of infections), with HPV16/18 accounting for 1.59% of infections. Age-stratified analysis revealed a U-shaped infection curve: peaks at 20–24 years (16.07%) and ≥ 65 years (11.84%), nadir at 45–49 years (8.94%; R²=0.89, p < 0.01). Cytological abnormalities occurred in 8.27% (1,746/21,112) of the patients, predominantly ASC-US (79.5%). The ≥ 65 years participants presented the highest abnormality rate (11.84% vs. other groups). Hr-HPV positivity correlated strongly with cytological severity (p < 0.001), increasing from NILM (7.84%) to HSIL (92.31%). HPV16/18 was more prevalent in high-grade lesions (HSIL: 38.46%; OR = 60.2 vs. NILM, 95% CI: 18.4–196.7). Conclusion Shannan has a distinct hr-HPV epidemiology characterized by a lower prevalence, U-shaped age distribution, and non-16/18 type dominance. The resurgence of infections/abnormalities in elderly women warrants age-tailored screening. These findings support prioritizing multivalent vaccines in this high-altitude population.